Review of "Female Devotion and Textile Imagery in Medieval English Literature" - Eren Bolat (Ideas: Journal of English Literary Studies)
This article reviews Anna McKay's "Female Devotion and Textile Imagery in Medieval English Literature," published by D. S. Brewer in 2024.